STRATEGI TALENT MANAGEMENT DAN DAMPAKNYA TERHADAP PENGEMBANGAN ASN DI KABUPATEN PARIGI MOUTONG - Ashari B; Andhyka Andhyka; Dela Safitri; Cahya Ervira Andani; Andi Budiman (LPPM STIE Muhammadiah Bandung, 2026)
This study aims to analyze the talent management strategy within the Parigi Moutong Regency Government and evaluate its impact on civil servant (ASN) development and organizational performance. Using a qualitative case study approach, the research involved in-depth interviews, observations, and document analysis at the Regional Civil Service and Human Resources Development Agency (BKPSDM) and selected regional work units (OPDs). The findings reveal that the implementation of talent management remains partial, focusing primarily on recruitment and basic training, while talent mapping and career management have yet to be optimized. Supporting factors include leadership commitment and the availability of basic regulations, whereas major obstacles consist of budget limitations, low digital literacy, and an administrative-oriented bureaucratic culture. Positive impacts are evident in the improved competencies of civil servants participating in competency-based training, though the limited coverage reduces its broader effectiveness. The study concludes that strengthening competency-based and technology-driven talent management systems is essential to enhance ASN competitiveness at the local level. Policy recommendations include digitalizing talent mapping, enhancing managerial capacity, and integrating career development programs with organizational needs.